2023
DOI: 10.3389/fonc.2023.987781
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of microvascular invasion in hepatocellular carcinoma based on preoperative Gd-EOB-DTPA-enhanced MRI: Comparison of predictive performance among 2D, 2D-expansion and 3D deep learning models

Abstract: PurposeTo evaluate and compare the predictive performance of different deep learning models using gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced MRI in predicting microvascular invasion (MVI) in hepatocellular carcinoma.MethodsThe data of 233 patients with pathologically confirmed hepatocellular carcinoma (HCC) treated at our hospital from June 2016 to June 2021 were retrospectively analyzed. Three deep learning models were constructed based on three different delineate meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several studies using AI or radiomic features extracted from gadoxetic acid-enhanced MRI, dynamic contrast enhanced MR, or contrast enhanced CT images tried to predict microvascular invasion in HCC and mass-forming CC ( 36 ). The AUCs ranged from 0.75 to 0.98 with most of the studies achieving AUCs higher than 0.85 ( 36 47 ). Notably, studies focused on peritumoral areas within the 5 cm to 10 cm range.…”
Section: Early Detection and Accurate Tumor Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using AI or radiomic features extracted from gadoxetic acid-enhanced MRI, dynamic contrast enhanced MR, or contrast enhanced CT images tried to predict microvascular invasion in HCC and mass-forming CC ( 36 ). The AUCs ranged from 0.75 to 0.98 with most of the studies achieving AUCs higher than 0.85 ( 36 47 ). Notably, studies focused on peritumoral areas within the 5 cm to 10 cm range.…”
Section: Early Detection and Accurate Tumor Classificationmentioning
confidence: 99%
“…One study underscored that patients without MVI experienced significantly prolonged recurrence-free survival (RFS). Validation sets were incorporated in all studies ( 36 47 ). As mentioned above, accurately predicting MVI before surgery can significantly influence surgical planning, including decisions regarding the extent of resection or the suitability of ablation treatments.…”
Section: Early Detection and Accurate Tumor Classificationmentioning
confidence: 99%
“…66 Some studies compared the predictive performance of different deep learning models between inputs or backbone in predicting MVI. 67 Such comparisons can be tedious as the models are independent, requiring ablation experiments to help humans truly understand the possible mechanisms. A multi-center and prospective validation study revealed that an efficient deep learning model based on EOB-enhanced MRI achieved superior performance in predicting MVI.…”
Section: Mri-based Deep Learning For Hccmentioning
confidence: 99%
“…Gao et al proposed an ensemble learning algorithm based on the different degree and attention mechanisms, combined with radiomics for MVI prediction with an AUC of 0.83 66 . Some studies compared the predictive performance of different deep learning models between inputs or backbone in predicting MVI 67 . Such comparisons can be tedious as the models are independent, requiring ablation experiments to help humans truly understand the possible mechanisms.…”
Section: Mri‐based Deep Learning For Hccmentioning
confidence: 99%
“…In the field of cell biology, 3D models based on embryoid body differentiation show advantages over 2D monolayer models, fostering enhanced cell interactions and promoting the induction of hematopoietic lineages [10]. In medical imaging, 3D deep learning models have demonstrated enhanced predictive performance over 2D models, specifically in predicting microvascular invasion in hepatocellular carcinoma [11]. In precision agriculture, the use of 3D reconstruction, such as laser scanning technology for maize plants, facilitates non-destructive crop monitoring and phenotypic analysis, revolutionizing agricultural practices [12].…”
Section: Introductionmentioning
confidence: 99%